Formação continuada dos diretores (gestores escolares) da rede pública estadual da educação básica do Paraná (2019-2022): implicações e perspectivas para uma educação crítica e emancipadora - Tramontin, Cheila Soethe (2023)
The present research has as its object of study and analysis the political-pedagogical guidelines of the continuing education of Directors (School Managers) of the state public network of basic education in Paraná, in the time frame of the 2019-2022 Management, under the mantle of New Public Management (NGP) – managerial management, adopted in the Government Plan of that period, it is clear that this management model defines the objectives present in the continuing education of Directors (School Managers) and exercises the measures and their materialization in schools. The research is of a social nature, with a qualitative, bibliographical and documental approach, having the methodological assumptions of historical-dialectical materialism. The Government Plan - Management 2019-2022; national and state legal documents that support continuing education for education professionals and school management; Continuing Education Program for Directors (School Managers) of this period, Notes, Letter, Newsletters of Associations, Representatives of Teachers and Employees of the State of Paraná; Universities; Forums. Its materialization will be presented through the programs and projects implemented by the Secretariat in the school, the instruments of control of the director's and teacher's work, and the standardization of the teaching and learning process. A priori, the government, through the Department of Education, outlines school management in the managerial model, and starts to meet the interests of the private sector in public education in Paraná. With reference to the theoretical foundations of HistoricalCritical Pedagogy, the aim is to point out possible elements of continued education for Directors (School Managers) in the conception of democratic management for a critical and emancipating education.